System optimization and validation to improve thin-layer chromatography of roselle calyces (Hibiscus sabdariffa L.) required by the Indonesian Herbal Pharmacopoeia Edition II - Bhujangga Agung Ayu Sri Kartika Dewi; Kartini Kartini (GarVal Editorial Ltda., 2023)
Context: Roselle (Hibiscus sabdariffa L.) is one of the traditional crude drugs monographed in the Indonesian Herbal Pharmacopoeia Edition II (IHP II). As per IHP II requirements, a TLC pattern should be used in its authentication. However, the TLC system described for this purpose does not produce a clear reference chromatogram, often leading to inconclusive results. Aims: To develop and validate TLC systems of H. sabdariffa calyces for a better-quality chromatogram than those listed in the IHP II, thereby facilitating crude drugs authentication. Methods: To optimize TLC for H. sabdariffa, sixteen systems, differing in stationary phase, mobile phase composition, and/or visualization reagent were tested. The TLC system was then validated using several parameters such as analyte stability during chromatography, analyte stability in the extract solution and on the TLC plate, stability of the derivatization result, and precision on a plate as well as intermediate precision. Results: Two systems (I and II) were successfully designed and applied to evaluate H. sabdariffa quality. System I used Si gel 60 F254 for the stationary phase, ethyl acetate-formic acid-glacial acetic acid-water (100:11:11:2) for the mobile phase, H. sabdariffa's ethanol extract (5%, 20 µL) for the test solution, cyanidin 3-O-glucoside (100 ppm, 4 µL) as a reference, no derivatization, and detection with visible light. System II combined Si gel 60 F254 for the stationary phase, ethyl acetate-formic acid-glacial acetic acid-toluene-water (80:11:11:20:19), H. sabdariffa's ethanol extract (5%, 20 µL) for the test solution, chlorogenic acid (1000 ppm, 2 µL) and caffeic acid (50 ppm, 2 µL) as references, the visualizing reagent NP/PEG, and investigation under 366 nm UV light. Conclusions: Both systems are simple but have good stability and precision, thus facilitating H. sabdariffa calyx authentication and paving the way for developing content analysis methods for H. sabdariffa markers.